An Empirical Analysis on the Scientific Operation Mode of Entrepreneurial Incubators in Higher Vocational Colleges - Leke Yang; Fei Wang (Advances in Multimedia)
In recent years, the concept of global business incubators has developed greatly. Entrepreneurship incubators have gradually developed into an important part of the market ecosystem in developed countries and emerging economies, and the innovation ability of higher vocational colleges has been continuously proven. In order to fully tap the potential of higher vocational college business incubators in higher vocational colleges, and improve the operation efficiency of higher vocational college business incubators. Then, to find out the current advantages of higher vocational college business incubators and explore a new operation path suitable for the development of higher vocational college business incubators, we selected 2016-2018 regional business incubators in higher vocational colleges as research samples and used the DEA model to calculate the operation efficiency of business incubators in higher vocational colleges. It is found that business incubators in higher vocational colleges play an important role in cultivating comprehensive and high-quality enterprises. The development of entrepreneurship incubators in higher vocational colleges in different regions is uneven. Compared with the overall operation efficiency of the eastern and central and western regions, the operation efficiency of entrepreneurial incubators in the northeastern region is low. By comparing the operating efficiency of professional incubators and comprehensive incubators in higher vocational colleges in the northeastern region, it is found that the operating efficiency of professional incubators is significantly higher than that of comprehensive incubators. It provides a reference for the transformation of the operation mode of entrepreneurship incubators in higher vocational colleges.